PENANAMAN NILAI-NILAI KARAKTER RELIGIUS PADA PESERTA DIDIK MELALUI KEGIATAN EKSTRAKURIKULER ROHIS DI SMA NEGERI 1 KOTA TIDORE KEPULAUAN - Umar, Sumiyati; Abdullah, Jainudin; Noe, Wahyudin; Bunta, Abd. Firman (Universitas Khairun, 2023)
This research was motivated by researchers concerns about the morals of the younger generation, especially school age, which are being degraded due to the negative impacts of globalization and technological advances. The development of technology in the information sector, especially the ease of accessing information from the internet, has resulted in the role of educators starting to shift, especially in developing students' behavior and morals. Therefore, it is important to carry out character education intensively, especially religious character as a basic bulwark in filtering outside culture or the negative impact of technological developments. Character education can be provided through classroom learning accompanied by religious extracurriculars, in this case spiritual, so that it is more intensive and comprehensive in forming good character. This research aims to describe the form of application of religious character values in religious extracurricular activities through spiritual organizations at SMA Negeri 1 Tidore Islands City. This research uses a qualitative approach with a case study method. The results of the research show that the form of application of religious character values through religious extracurricular activities of spiritual organizations at SMA Negeri 1 Tidore Islands City is carried out in the form of: 1) the application of religious character values is instilled based on indicators of religious character, namely the value of worship, trustworthiness and sincerity, moral and discipline values, as well as exemplary values; 2) implemented through religious extracurricular activity programs, namely daily activity programs, weekly activity programs and annual activity programs. The supporting factors in implementing religious character values through spiritual organizations include: 1) support from the school; 2) the response and development of students who are active in participating in spiritual extracurricular activities; 3) supporting facilities and infrastructure. Meanwhile, inhibiting factors in implementing spiritual activities include: 1) there is still a small number of students who do not participate in spiritual activities; 2) the time discipline of spiritual administrators is considered inconsistent.